In vitro penetration of vancomicin through biofilms of coagulase negative staphylococci isolated from a hospital of Lima-Peru - León, Sergio D. (2017)
Infections associated with biofilm producer bacteria, such as coagulase negative staphylococci (CoNS) are difficult to treat, because they are more resistant to antibiotics than its plactonic form, perhaps because do not allow an optimal drug diffusion. This paper aims contribute to knowledge of resistance strategies by these microbial communities, considering as objectives, isolate biofilm producer CoNS from venous catheters(CVC), induce biofilms in vitro production and evaluate vancomycin penetration through of them. 121 CVC were collected, from Intensive Care Unit of Hospital Nacional Guillermo Almenara Irigoyen. 46 strains were identified as CoNS, being 46% of them, biofilm producers according to Congo Red agar method; Staphylococcus epidermidis ATCC 35984 (biofilm forming bacteria) and Staphylococcus epidermidis ATCC 12228 (non-biofilm forming bacteria) were used as controls. Vancomycin penetration through biofilms induced in vitro was evaluated by the Ander et al. method, observing that the antibiotic penetrated about 57,5% of its concentration through biofilms after six hours of exposure, while negative control diffused 92,4%. Almost, was observed that antibiotic continued to spread until 24 hours, reaching an average penetration of 82,2%. Statistical analysis showed no significant differences between counts of colonies of viable bacteria in the biofilms exposed to antibiotic and their respective controls.